Intraoperative Nodal Palpation is a Mandatory Component of Sentinel Lymph Node Biopsy for Breast Cancer: IOP node palpation - Noguchi, Masakuni; Inokuchi, Masafumi; Morioka, Emi; Haba, Yusuke; Shioya, Akihiro; Yamada , Sohsuke; Iida, Yasuo (Archives of Breast Cancer, 2024)
Background: In the era of Z-0011, it is mandatory to decrease not only the false negative rate (FNR) of sentinel lymph node (SLN) biopsy but also the risk of residual metastatic nodes after SLN biopsy. Method: SLN biopsy with intraoperative nodal palpation (INP) was performed in patients with clinically node-negative (cN0) breast cancer. All identified blue and hot nodes were removed as blue/hot SLNs, and any suspicious palpable nodes were removed as palpable SLNs. Nodes that were incidentally removed with neighboring the blue/hot SLNs were classified as para-SLNs. Patients with positive SLNs on frozen section underwent axillary lymph node dissection (ALND) except for patients who met the Z-0011 and AMAROS criteria for exemption. Results: Palpable SLNs and para-SLNs were identified in 202 patients. Of 200 patients, excluding 2 patients only with palpable SLNs, 46 patients had involvements of blue/hot SLNs, and 14 had palpable and para-SLNs harboring additional metastasis. When false negative rate (FNR) was calculated based on blue/hot SLNs and palpable SLNs, the additional use of INP resulted in a FNR of 45.2%. Subsequently, ALND was performed in 43 patients with positive blue/hot or palpable SLNs. Residual nodal involvement was found in 28 (65%) of 43 patients after removing blue/hot SLNs. However, after removing palpable SLNs, the rate of residual nodal metastases significantly decreased from 65% (28/43) to 36% (13/36) (p=0.0133). Conclusion: INP decreased both the FNR of SLN biopsy and the risk of residual metastatic nodes after SLN biopsy.